Kegiatan Penangkapan Ikan di Sungai Kampar, Desa Buluh Cina, Riau - sari, Yesi Puspita; Wedari, Latifah Sri; Sawestri, Sevi; Hukmanan Rais, Aroef (Seminar Nasional Lahan Suboptimal, 2024)
Sari, Y. P., Wedari, L. S., Sawestri, S., & Rais, A. H. (2024). Fishing activities in The Kampar River, Buluh Cina Village, Riau. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 523-532). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The Kampar River is one of the important rivers in Riau, where it is the main contributor to the District's Gross Regional Domestic Income (GRDP) Kampar. The status of fish resource utilization in the Kampar River is a major concern. The aimed of this research was to obtain data on capture fisheries activities which include fishing gear type, production and fishing gear rate, also fish catch composition in the waters of the Kampar River, Buluh Cina Village, Riau. The research was conducted from March to October 2022. Fish sampling involved 10 fishers who recorded their catches (enumerators). The total catch value was calculated form the total catch of enumerator fishers in one month. Furthermore, the calculation of capture rate value for each month was obtained from the relationship between fishing effort compared to catch. Catch data was obtained from 11 types of fishing gear. There were three groups of fishing gear, namely the hook and line group (pancing, rawai, dan tajur), the trap/pot trap group (bubu, lukah, pengilar, sempirai, and toban), and the nets/gill nets group (gill nets, trawls, and cast nets). The research results showed that gill nets and sempirai fishing gear can be used throughout the year and have the highest production results. Cast nets type fishing gear has the highest catch rate. A total of 26 species including fish and shrimp were recorded during the research. The catch was dominated by motan fish (Tynnichys polylepis) 27.02%, pawe (Osteochilus kapperil) 22.30%, and snakehead (Channa striata) 11.05%.